Cystic acne in women who present excess of testosterone because of social reasons and not of pathological diseases. An attempt to treat this malaise by natural remedies and the discovery of a suggestive equation to solve to know how many days of treatment are required for remission - Piotr Brzeziński; Lorenzo Martini (Our Dermatology Online, 2018)
Aims of our research is to demonstrate that by the same way women who have high testosterone levels show always an elevate sex drive, women who indeed have a high sex drive (often because they cannot have regular sexual intercourses with men or are forced to live and work in competitive fields, as Army or prisons or monasteries) have always high testosterone levels. Excess of testosterone in woman (more than 0.8ng/ml) may lead to cystic acne and our purpose is to treat cystic acne in this type of women, endowed by elevated serum testosterone levels.